2020
DOI: 10.3390/ijerph17155388
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parental Remote Migration and Parent-Child Relation Types on the Psychological Resilience of Rural Left-Behind Children in China

Abstract: Using survey data of middle school students from Ye county in Henan province and Chenggu and Ningqiang county in Shaanxi province, China, adopting latent class analysis and hierarchical linear regression, this study analyzes the impact of parental remote migration and parent-child relation types on the psychological resilience of rural left-behind children. The results show that: Only mother’s remote migration has a significantly negative impact on the psychological resilience of rural left-behind children, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…Groups vary in coping styles and social support, and these differences are affected by individual characteristics and external environmental factors [23]. Previous literature indicates that LBC are characterized by an unwillingness to express their troubles to their guardians; their social support mainly comes from peers, incomplete parent-child relations, and limited and autonomous social interaction [24,25]. However, our understanding of the subtle, indirect and complex relationship between individual characteristics and external environmental factors and coping styles is still incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Groups vary in coping styles and social support, and these differences are affected by individual characteristics and external environmental factors [23]. Previous literature indicates that LBC are characterized by an unwillingness to express their troubles to their guardians; their social support mainly comes from peers, incomplete parent-child relations, and limited and autonomous social interaction [24,25]. However, our understanding of the subtle, indirect and complex relationship between individual characteristics and external environmental factors and coping styles is still incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…Rural to internal urban migration in China brought massive changes in migrant family functioning (Jia and Tian, 2010 ; Jingzhong and Lu, 2011 ; Hu, 2016 ; Mu and Hu, 2016 ; Liang et al, 2017 ; Hu, 2019 ; Tian et al, 2017 ; Xiaofeng et al, 2018 ; Chen et al, 2019 ; Lu et al, 2019 ; Zhang et al, 2019 ; Liu et al, 2020 ; Shi et al, 2021 ). Since the early 1980s, China’s urbanization expansion plan and relaxing household registration system ( hukou ) have stimulated economic growth (Su et al, 2017 ), attracting rural peasant workers to urban areas to seek better job opportunities and lifestyles (Jingzhong and Lu, 2011 ; Wen and Lin, 2012 ; Wu and Zhang, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1980s, China’s urbanization expansion plan and relaxing household registration system ( hukou ) have stimulated economic growth (Su et al, 2017 ), attracting rural peasant workers to urban areas to seek better job opportunities and lifestyles (Jingzhong and Lu, 2011 ; Wen and Lin, 2012 ; Wu and Zhang, 2017 ). This dramatic migration decreased the impoverishment of rural areas and encouraged laborers to move from rural to urban areas to satisfy the cities’ need for labor (Jingzhong and Lu, 2011 ; Wen and Lin, 2012 ; Wu and Zhang, 2017 ; Su et al, 2017 ; Liu et al, 2020 ; Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researches on the mental health of left-behind children indicated that factors such as children’s age [ 12 ], gender [ 13 ], personality and self-esteem [ 7 ], self-efficacy [ 14 ], types of family migration [ 15 ], caregivers’ individual factors (such as age, educational attainment, socioeconomic status, etc.) [ 9 , 11 ], duration of separation [ 16 , 17 ], communication duration and frequency [ 18 ], as well as coping strategies in dealing with daily stressors [ 19 ] all had significant influence. In addition, some studies analyzed the effect of parents’ migration on their left-behind children’s academic performance.…”
Section: Introductionmentioning
confidence: 99%